1975
DOI: 10.3382/ps.0540054
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Five Strains of Broilers in a Four-Tier Cage System with Plastic Mat Floors

Abstract: Five strains of broilers were reared in cages and in floor pens. The cages were arranged in four tiers in a back-to-back arrangement. Plastic mats were inserted over the wire floors in the finisher cages and conventional rice hull litter was used in the floor pens. Within the cage system, significant differences were found between strains, tiers, sex and the strain x sex interaction for 8-week body weight (P < 0.01). There were significant differences among strains as to enlarged feather follicles and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
2

Year Published

1976
1976
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 5 publications
4
20
0
2
Order By: Relevance
“…The strain x sex interaction for weight at 8 weeks found in this trial agrees with the result of Andrews et al (1975). Furthermore, the knowledge that the food conversion efficiency of females is more affected than that of males when kept at high stocking rates shows also the need for definition of optimum densities for each sex within a strain.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The strain x sex interaction for weight at 8 weeks found in this trial agrees with the result of Andrews et al (1975). Furthermore, the knowledge that the food conversion efficiency of females is more affected than that of males when kept at high stocking rates shows also the need for definition of optimum densities for each sex within a strain.…”
Section: Discussionsupporting
confidence: 81%
“…There are also data to indicate differences in performance between broiler strains reared in cages (Andrews et al, 1975), although information in this field is somewhat scarce.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, Elibol 18 (CBG 1792 -FBG 1745 g), Reece et al 19 and Andrews et al 20 indicated that the final body weights of Group CBG were higher than those of Group FBG and that the two groups differed from each other significantly. Furthermore, Andrews 21 (CBG 1572 -FBG 1573 g), Andrews et al 22 (CBG 1513 -FBG 1485 g), and Athar et al 23 (CBG 2000 -FBG 1910 g) indicated that Groups FBG and CBG did not display any statistically significant difference from each other in terms of final body weights.…”
Section: Discussionmentioning
confidence: 99%
“…Yine araştırıcılar yukarda sözü edilen çevresel faktörlerı e genotipler arasında ilgili verim özeııikleri için genotip x çevre interaksiyonlarını canlı ağırlık, ilk yumurtlama yaşı, yumurta sayısı ve yumurta ağırlığı için önemli bulurken (4,5,13,19,23,32), yumurta kabuk ağır-lığı için interaksiyonları önemsiz bildirmişlerdir. Ancak bazı araştırı-cılar genotip x çevre interaksiyonlarının bazı özeııikler için önemli olduğunu açıklamaktadır (2,16,22).…”
Section: Ummary: This Investigation Was Held To Estimate the Environmunclassified